Strategi ketidaksantunan bahasa juri dalam rancangan realiti / Anitha Xavior - Anitha, Xavior (2017)
This is a pragmatic research that studies impoliteness of juries in a Tamil reality show. Based on the literature review, researches on impoliteness in reality shows are limited and has never been done in Tamil language. Therefore, this research is done to ignite the gap of research on impoliteness in a reality show. The objective of this research is to study the impoliteness among juries of a reality show. Discussion of this research is focused on the impoliteness strategy and how the impoliteness of the juries threatens the participant’s face reaction. Language is limited in this research whereby, the data is translated into Malay language but the analysis is based on Tamil language. The researcher used the impoliteness strategy theory of Culpeper (2005) as well as Goffman’s theory (1967) as the framework of this research. The research method is qualitative based on descriptive. This research’s data is based on 145 texts from three seasons of the reality show that was chosen. The research instruments are video recording and interview. The result of the research found that two of the reality show juries used impolite language strategy in their conversation that resulted in face threatening action. The impolite strategy dominates the research data. Lastly, the interview result has justified the research outcome that the juries used threatening face action to threaten participants’ face reaction and resulting in impoliteness action.